2023
DOI: 10.3389/fendo.2023.1201198
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediated apoptotic death of colon cancer cells: therapeutic potential of plant derived alkaloids

Vinod K. Nelson,
Mohana Vamsi Nuli,
Juturu Mastanaiah
et al.

Abstract: Colorectal cancer (CRC) is one of the most deaths causing diseases worldwide. Several risk factors including hormones like insulin and insulin like growth factors (e.g., IGF-1) have been considered responsible for growth and progression of colon cancer. Though there is a huge advancement in the available screening as well as treatment techniques for CRC. There is no significant decrease in the mortality of cancer patients. Moreover, the current treatment approaches for CRC are associated with serious challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…ROS cause CRC initiation via inflammation, DNA damage, epithelial-to-mesenchymal transition, apoptosis, and angiogenesis [37]. ROS also result in the initiation of mutations in various proteins involved with regulating the cell cycle (proto-oncogenes), including p53, Ras, and c-Myc, leading to oncogene activation [12]. Colibactin produced by enterotoxigenic E. coli with polyketide synthesis (pks) genomic islands alters cell cycle progression and induces DNA damage [21].…”
Section: Dysbiosis Initiates Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…ROS cause CRC initiation via inflammation, DNA damage, epithelial-to-mesenchymal transition, apoptosis, and angiogenesis [37]. ROS also result in the initiation of mutations in various proteins involved with regulating the cell cycle (proto-oncogenes), including p53, Ras, and c-Myc, leading to oncogene activation [12]. Colibactin produced by enterotoxigenic E. coli with polyketide synthesis (pks) genomic islands alters cell cycle progression and induces DNA damage [21].…”
Section: Dysbiosis Initiates Colorectal Cancermentioning
confidence: 99%
“…LPS is associated with cell adhesion, cell degradation, and cell invasion in CRC metastasis [43]. Studies have demonstrated that LPS-associated inflammation increases the activity of oncogenic genes and the cell proliferation of CRC in IBD animal models [12]. LPS also alters the integrity of the intestinal barrier by disrupting the tight junctions, leading to CRC tumorigenesis, tumor growth, leakage of microbial products into the bloodstream, systemic inflammation, and metabolic endotoxemia (ME) [43].…”
Section: Dysbiosis Causes Inflammatory Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few medicinal plants have been evaluated extensively for their antidepressant mechanism of action (Maina et al, 2020). An array of studies has revealed that medicinal plants may hold the key to discovering lead chemicals for innovative therapeutics against several neurological disorders (Wal et al, 2022;Wal et al, 2023 A.;Wal et al, 2023 P.;Alrouji et al, 2023;Nelson et al, 2023). Hence, research in this area could help develop effective management of psychiatric disorders in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The increased mitochondrial dysfunction makes the cancer cells more vulnerable to oxidative stress than normal cells. Therefore, a minor rise in ROS levels caused by external stimuli can cause cancer cell death through a variety of death pathways [ 30 ]. This mechanism has led to the development of pro-oxidant therapy, which uses agents to cause oxidation-induced cell death, as a potent method of cancer treatment [ 31 ].…”
Section: Introductionmentioning
confidence: 99%